A scientometric analysis of the 100 most cited articles on magnetic resonance guided focused ultrasound - Garg, Kanwaljeet; Ranjan, Manish; Krishna, Vibhor; Singh, Manmohan; Rezai, Ali (Frontiers in Human Neuroscience, 2022)
Background: Diagnostic ultrasound has long been a part of a physician's armamentarium, but transcranial focused ultrasound (FUS) is an emerging treatment of neurological disorders. Consequently, the literature in this field is increasing at a rapid pace. Objective: This analysis was aimed to identify the top-cited articles on FUS to discern their origin, spread, current trends highlighting future impact of this novel neurosurgical intervention. Methods: We searched the Web of Science database on 28th May 2021 and identified the top 100 cited articles. These articles were analysed with various scientometric parameters like the authors, country of corresponding author, journal of publication, year of publication. Citation based parameters including total citations, mean citations per article and mean citations, citation count, and the citation per year, citations per year and co-authors per document were studied as well in addition to Hirsch h-index, g-index, m-index, Bradford’s Law, Lotka's law and Collaboration index. . Results: The 100 top-cited articles were published between 1998 and 2019 in 45 different journals. The average citations per document and citations per document per year were 97.78 and 12.47, respectively. The most prolific authors were Hynynen K (Medical Biophysics - Toronto), Elias WJ (Neurosurgery - Virginia), Zadicario (InSightec). The Journal of Neurosurgery published the most top-cited articles (n=11), and most articles originated from the United States, followed by Canada. Among individual institutions, the University of Toronto was the most productive. Conclusions: FUS is an emerging treatment of neurological disorders. With its increasing application, the FUS literature is increasing rapidly. Eleven countries contributed to the top 100 cited articles, with the top 2 countries (the USA and Canada) contributing to more than half of these articles.